Effect of zinc sulfate supplementation on metallothionein levels in rat heart tissue with induced ischemia-reperfusion injury - Yazgan, Betul; Baltaci, Abdulkerim Kasim; Mogulkoc, Rasim; Avunduk, Mustafa Cihat; Sahna, Engin (Biointerface Research Applied Chemistry, 2018)
Metallothioneins are remarkable proteins with regard to their role in the regulation of intracellular zinc balance and mediation of the physiological effects of zinc, as well as their antioxidant effects. The objective of the present study is to examine how zinc supplementation impacts metallothionein levels in ischemia-reperfusion injury in rats. The study involved heart tissues obtained from 30 Wistar-Albino adult male rats already used in another project. Experimental animals were equally divided into three groups as follows: Group 1: Control (H-Cont); Group 2: Heart Ischemia/Reperfusion (H-I/R); and Group 3: Zinc supplemented Ischemia/Reperfusion (H/Zn-I/R). Cardiac ischemia-reperfusion procedures were carried out under general anesthesia. In the zinc-supplemented cardiac I/R group (Group 3), the animals were supplemented with 5 mg/kg/day intraperitoneal (i.p.) zinc sulfate per rat for 21 days. At the end of the procedures, all animals were decapitated and heart tissues were collected. The tissues were subjected to immunohistochemical staining procedures using rat metallothionein antibody. The stained preparations were photographed and cells stained with metallothionein were counted at a light microscope to calculate their percentages. The analyzed heart tissue samples of the groups did not have any significant difference in terms of their metallothionein levels. Results obtained from the study indicate that 21-day zinc supplementation does not have a critical effect on metallothionein synthesis in cardiac ischemia-reperfusion. This result may be attributed to the dose of zinc, length of supplementation and/or duration of ischemia-reperfusion.
Keywords: Cardiac ischemia-reperfusion; zinc supplementation; metallothionein; rat